2022
DOI: 10.3390/ijerph192114229
|View full text |Cite
|
Sign up to set email alerts
|

Patient Involvement in Shared Decision-Making: Do Patients Rate Physicians and Nurses Differently?

Abstract: Background. Shared decision-making implies that patients and healthcare professionals make decisions together about clinical exams, available treatments, choice of options, and the benefit or downside of every choice. Patients involved in the shared decision-making process are more compliant with treatments and have a reduced risk of complications related to the pathology. In Italy, patient involvement in caring processes is still barely investigated. Aim. To investigate patients’ perceptions about shared deci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 46 publications
0
7
0
Order By: Relevance
“…This can encourage patients to take an active role in their care, thereby enhancing their sense of control, reducing anxiety, and promoting better coping strategies. Moreover, an informed patient may be better equipped to manage potential complications, leading to improved health-related quality of life and potentially reducing hospital readmissions (Galletta et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This can encourage patients to take an active role in their care, thereby enhancing their sense of control, reducing anxiety, and promoting better coping strategies. Moreover, an informed patient may be better equipped to manage potential complications, leading to improved health-related quality of life and potentially reducing hospital readmissions (Galletta et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…Secondly, comprehensive nursing care aims to facilitate informed decision-making, aiding patients in understanding their disease, treatment options and potential side effects (Galletta et al, 2022). This can encourage patients to take an active role in their care, thereby enhancing their sense of control, reducing anxiety, and promoting better coping strategies.…”
Section: Discussionmentioning
confidence: 99%
“…This collaborative approach aligns with SDM frameworks like Elwyn et al's "three-talk model" and the Ottawa Decision Support Framework, which focus on structured decision-making phases and informed deliberation [ 10 , 42 ]. The significance of such collaborative models, especially SDM, is underscored by research from Pieterse AH et al [ 16 , 38 ]. These studies highlight the crucial role of patient-physician collaboration and explore the challenges and facilitators encountered in implementing SDM across varied healthcare settings.…”
Section: Introductionmentioning
confidence: 99%
“…A quantitative Italian study showed that less than half of the patients indicated that nurses provided the necessary information. Additionally, patients indicated that nurses should be sensitised to involve patients in the decision‐making process (Galletta et al., 2022). In the Netherlands, where SDM has received much attention—including through a national campaign called ‘To Decide Together’—behavioural and cultural change in decision‐making is still ongoing (Van Der Weijden et al., 2022).…”
Section: Introductionmentioning
confidence: 99%